Thermo‐physical properties of synthetic mucus for the study of airway clearance. Issue 11 (14th August 2017) - Lafforgue, O.; Bouguerra, N.; Poncet, S.; Seyssiecq, I.; Favier, J.; Elkoun, S.
Abstract: In this article, dynamic viscosity, surface tension, density, heat capacity and thermal conductivity, of a bronchial mucus simulant proposed by Zahm et al., Eur Respir J 1991; 4: 311–315 were experiementally determined. This simulant is mainly composed of a galactomannan gum and a scleroglucan. It was shown that thermophysical properties of synthetic mucus are dependant of scleroglucan concentrations. More importantly and for some scleroglucan concentrations, the syntetic mucus, exhibits, somehow, comparable thermophysical properties to real bronchial mucus. An insight on the microstructure of this simulant is proposed and the different properties enounced previously have been measured for various scleroglucan concentrations and over a certain range of operating temperatures. This synthetic mucus is found to mimic well the rheological behavior and the surface tension of real mucus for different pathologies. Density and thermal properties have been measured for the first time. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3025–3033, 2017.